Relationship between tea intake and cedar pollen allergy: a population-based cross-sectional study - Nozomi Aoki; Mai Suzuki; Yuki Sato; Hirohide Yokokawa; Toshio Naito (Journal of Nutritional Science)
Tea intake has been associated with health benefits, including potential beneficial effects of catechin-containing teas on allergic symptoms. However, large-scale epidemiological studies on the relationship between tea intake and allergic symptoms have been limited. The present study aimed to examine the relationship between the frequency of tea intake and cedar pollen allergy, which is a major cause of seasonal hay fever in Japan, in a large Japanese epidemiological cohort. Data on cedar pollen antibody levels assessed by blood tests and frequency of tea intake (green tea, coarse tea, oolong tea, and black tea) by a self-administered questionnaire from 16,623 residents in the Tohoku region of Japan were used in this study. The association between frequency of tea intake (less than once a week, 1–6 times/week, and more than once a day) and serum levels of cedar pollen-specific IgE (lumicount, LC: negative, 0–1.39; positive, ≥1.40) was analysed using a logistic regression model. Green tea intake (≥vs. <1/day) was inversely associated with cedar pollen-specific IgE (adjusted OR = 0.81, 95% CI, 0.70, 0.94). No statistically significant association between cedar pollen-specific IgE and frequency of tea intake was found for other types of tea. Our results suggest that green tea intake may be associated with lower cedar pollen-specific IgE positivity.